2013
DOI: 10.1128/cvi.00047-13
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus Ingestion Promotes Innate Host Defense in an Enteric Parasitic Infection

Abstract: Enteric parasite infections around the world are a huge economic burden and decrease the quality of life for many people. The use of beneficial bacteria has attracted attention for their potential therapeutic applications in various diseases. However, the effects of beneficial bacteria in enteric parasitic infections remain largely unexplored. We investigated the effects of ingestion of Lactobacillus rhamnosus (JB-1) in a model of enteric nematode (Trichuris muris) infection. C57BL/6 (resistant to infection), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Furthermore, Lactobacillus casei increased the susceptibility of rodents to intestinal nematodes, 70 whereas Lactobacillus rhamnosus reduced the duration of nematode infection. 71 Our findings suggest that vaginal Lactobacillus may increase susceptibility to Ascaris or prolong duration of infection, an observation not previously reported.…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, Lactobacillus casei increased the susceptibility of rodents to intestinal nematodes, 70 whereas Lactobacillus rhamnosus reduced the duration of nematode infection. 71 Our findings suggest that vaginal Lactobacillus may increase susceptibility to Ascaris or prolong duration of infection, an observation not previously reported.…”
Section: Discussionsupporting
confidence: 67%
“…The reduction of IL‐10 mRNA promoted by S. boulardii may have helped to maintain the higher IL‐12 levels and hold back the establishment of infection in supplemented group, since the increase of IL‐10 act by antagonizing the effects of IL‐12 that could favour T. canis infection . In another study, the probiotic Lactobacillus rhamnosus promoted increase of IL‐10 levels, which was related to increase of Trichuris muris expulsion from the gut of mice . In both studies, we noted a protective role of the probiotics tested, although in T. canis experiment IL‐10 reduction was beneficial whereas in T. muris experiment the opposite was observed.…”
Section: Discussionmentioning
confidence: 60%
“…Furthermore, the beneficial effect of IL‐10 on T. muris expulsion is caused by the fact that parasites present in the intestinal lumen are eliminated by the action of Th2 cytokine and IL‐10 McClemens et al . While in T. canis infection, the increase of IL‐10, with consequent reduction of Th1 cells, may cause immunosuppression and favour infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to evidence of enhanced mucus secretion in response to intestinal microbes, studies have shown altered goblet cell responses in germfree animals (18,19,41). In our recent study, we observed that treatment with beneficial bacteria L. rhamnosus (JB-1) promotes T. muris expulsion in association with upregulation of goblet cells (42). It was also shown that depletion of flora with antibiotics reduced the worm burden in T. muris infection in susceptible mice (43).…”
Section: C3gntmentioning
confidence: 67%